2012
DOI: 10.1186/1471-244x-12-87
|View full text |Cite
|
Sign up to set email alerts
|

The effect of clinician-patient alliance and communication on treatment adherence in mental health care: a systematic review

Abstract: BackgroundNonadherence to mental health treatment incurs clinical and economic burdens. The clinician-patient alliance, negotiated through clinical interaction, presents a critical intervention point. Recent medical reviews of communication and adherence behaviour exclude studies with psychiatric samples. The following examines the impact of clinician-patient alliance and communication on adherence in mental health, identifying the specific mechanisms that mobilise patient engagement.MethodsIn December 2010, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
142
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(152 citation statements)
references
References 57 publications
4
142
0
6
Order By: Relevance
“…Disparities in minority groups' utilization and experiences of mental health services as well as patient-provider relationships are welldocumented (Alegria et al, 2008;DHHS, 2001;McGuire & Miranda, 2008). These inequalities have been attributed to provider's lack of empathy, cultural competence, provider's racial bias, as well as patients' distrust in the health care system (Constantine, 2007;Cooper et al, 2012;DHHS, 2001; L. Thompson & McCabe, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Disparities in minority groups' utilization and experiences of mental health services as well as patient-provider relationships are welldocumented (Alegria et al, 2008;DHHS, 2001;McGuire & Miranda, 2008). These inequalities have been attributed to provider's lack of empathy, cultural competence, provider's racial bias, as well as patients' distrust in the health care system (Constantine, 2007;Cooper et al, 2012;DHHS, 2001; L. Thompson & McCabe, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Another possible factor may be rapport between provider and patient, as other studies have shown that the quality of the provider-patient relationship, particularly surrounding communication and empathy, are positive predictors of medication adherence. [41][42][43] Psychiatrists often receive more training in patient engagement and motivational interviewing, and perhaps were able to develop better rapport with patients with depression.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Pharmacists often assume that physicians explain the importance of the medications they prescribe, as well as assume that physicians routinely inquire about their patients' problems with therapies. This is often not the case.…”
Section: A J P E a C C E P T E D D R A F Tmentioning
confidence: 99%
“…These difficulties are lessened when the patient has a supportive, trusting relationship with their health care provider. 31 Thompson (2012) described how having an empathetic, respectful provider who is a good listener improves patients' adherence to therapy. Results from our study indicated that both patients and students were in agreement regarding the top three reasons for medication non-adherence -lending credence to student perceptions on these factors.…”
Section: A J P E a C C E P T E D D R A F Tmentioning
confidence: 99%